2013
DOI: 10.5194/bg-10-1625-2013
|View full text |Cite
|
Sign up to set email alerts
|

Decreased carbon limitation of litter respiration in a mortality-affected piñon–juniper woodland

Abstract: Microbial respiration depends on microclimatic variables and carbon (C) substrate availability, all of which are altered when ecosystems experience major disturbance. Widespread tree mortality, currently affecting piñon–juniper ecosystems in southwestern North America, may affect C substrate availability in several ways, for example, via litterfall pulses and loss of root exudation. To determine piñon mortality effects on C and water limitation of microbial respiration, we applied field amendments (sucrose and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…These effects were not linked to abiotic factors known to be important in regulating denitrification (Wallenstein et al ., ), such as humidity or nitrate availability, which were identical in all samples (data not shown). However, microbial (aerobic or anaerobic) respiration is highly dependent on carbon availability, and under limiting conditions, carbon amendments often lead to increases in DEA and SIR (Tenuta et al ., ; Berryman et al ., ). To avoid the potentially masking effect of C input on denitrification, Schimann et al .…”
Section: Discussionmentioning
confidence: 99%
“…These effects were not linked to abiotic factors known to be important in regulating denitrification (Wallenstein et al ., ), such as humidity or nitrate availability, which were identical in all samples (data not shown). However, microbial (aerobic or anaerobic) respiration is highly dependent on carbon availability, and under limiting conditions, carbon amendments often lead to increases in DEA and SIR (Tenuta et al ., ; Berryman et al ., ). To avoid the potentially masking effect of C input on denitrification, Schimann et al .…”
Section: Discussionmentioning
confidence: 99%
“…They found that litter respiration responded to water availability at both treatment and control sites, and that soil respiration decreased at the site with experimental mortality. These results demonstrate ecosystem-level consequences of tree mortality that differs as a function of water availability (Berryman et al, 2013). Yue et al (2013) compared observations from post-fire vegetation trajectories in the boreal forest with simulations from the process-based ORCHIDEE (Organizing Carbon and Hydrology In Dynamic Ecosystems) vegetation model and supported the notion that the increase in atmospheric CO 2 concentrations and vegetation recovery were jointly responsible for current carbon-sink conditions.…”
Section: Disturbance Legacymentioning
confidence: 65%
“…Berryman et al (2013) tested the impacts of experimental pinyon pine (Pinus edulis Englem.) mortality on microbial respiration.…”
Section: Disturbance Legacymentioning
confidence: 99%
“…Disturbance-induced tree mortality regulates the forest carbon balance, but tree mortality and its carbon consequences are not well represented in ecosystem models (Bond-Lamberty et al, 2015). Bond-Lamberty et al (2015) tested whether three ecosystem models -the classic bigleaf model Biome-BGC (BioGeochemical Cycles) and the gap-oriented models ZELIG, a gap model, and ED (ecosystem demography) -could reproduce the resilience of forest ecosystems to moderate disturbances. The models replicated observed declines in aboveground biomass well but could not fully capture observed post-disturbance carbon fluxes.…”
Section: Disturbance Legacymentioning
confidence: 99%